Prognosis and predictors of hepatocellular carcinoma in elderly patients infected with hepatitis B virus. Issue 12 (31st August 2017) - Osawa, Mitsutaka; Akuta, Norio; Suzuki, Fumitaka; Fujiyama, Shunichiro; Kawamura, Yusuke; Sezaki, Hitomi; Hosaka, Tetsuya; Kobayashi, Masahiro; Kobayashi, Mariko; Saitoh, Satoshi; Arase, Yasuji; Suzuki, Yoshiyuki; et al.
Abstract : With rapidly aging population in the world, many elderly patients present with hepatitis B virus (HBV) infection. We conducted a retrospective cohort study involving 359 untreated HBV patients aged 60 and older who were free of hepatocellular carcinoma (HCC) and acute hepatitis at the initial visit, and examined the incidence of HCC and liver‐related mortality rate. During the follow‐up period of 7.9 years (range, 0‐25 years), 26 patients (7.2% of patients) developed HCC, 20 patients died from liver‐related diseases (61% of total deaths), including HCC, liver failure, and gastrointestinal bleeding. The cumulative rates of HCC at years 5, 10, and 15 were 6.5%, 15.6%, and 15.6%, respectively. The cumulative rates of mortality from liver‐related diseases at years 5, 10, 15 were 3.3%, 12.3%, and 15.7%, respectively. Multivariate analysis identified HBV DNA (≥5.0 Log IU/mL), male gender, and FIB4‐Index (≥3.6) as significant independent risk factors for HCC, and alpha‐fetoprotein (≥10 ng/mL) as significant independent predictors of liver‐related mortality. We conclude that high levels of HBV DNA, progression of liver fibrosis, and male gender are independent risk factors of HCC in untreated patients infected with HBV aged 60 and older.